PUBLIC-PRIVATE PARTNERSHIP IN MANAGEMENT OF CONSTRUCTION DEVELOPMENT PROGRAMS IN UKRAINE - TOPAZLY, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the role of public-private partnership (PPP) in the implementation of construction sector development programs in Ukraine, which is an important direction for ensuring sustainable economic growth and infrastructure modernization. The main PPP models that can be applied in construction are identified, such as concession agreements, BOT (build-operate-transfer) mechanisms, DBO (design-build-operate) and others. The current state of regulatory regulation of PPP in the construction industry is analyzed, key problems that hinder effective interaction between the state and the private sector are identified, including the complexity of regulatory procedures, insufficient level of institutional support, high risks for private investors and limited access to long-term financing. Special attention is paid to the analysis of financial mechanisms that can contribute to the development of PPP in the construction sector, in particular, the Tax Increment Financing (TIF) mechanism, which allows compensating investors’ costs by increasing tax revenues from newly created infrastructure facilities. Successful examples of PPP implementation in Ukraine are considered, including transport and utility infrastructure, as well as social projects. Based on the research conducted, the main directions for improving PPP mechanisms in construction are formulated, including simplifying the regulatory environment, expanding the financial capabilities of private investors, introducing risk management mechanisms, and strengthening state support for such initiatives. It is concluded that the effective use of PPP in construction can become a powerful tool for infrastructure modernization, improving the investment climate, and creating new jobs. However, to achieve these results, it is necessary to implement comprehensive reforms aimed at eliminating administrative and financial barriers that hinder the development of partnership between the state and business. The relevance of the study of public-private partnership in construction is due to the need to improve public administration mechanisms in this area, optimize financial flows, and increase the efficiency of the implementation of construction programs. The purpose of this article is to analyze the current state of PPP in the construction sector of Ukraine, identify the main problems and develop recommendations for improving mechanisms for cooperation between the state and business. To achieve this goal, the article considers the theoretical foundations of public-private partnership, analyzes the current regulatory framework, examines successful examples of PPP implementation in construction, and identifies the main problems that hinder its development. Based on the analysis, recommendations are formulated for improving PPP mechanisms in the construction sector of Ukraine, in particular in the areas of simplifying the regulatory environment, introducing modern financial instruments, and strengthening institutional support.